(3eHGOF GdeMGSHI GdeGdjIs - (3eSYO eMehO(B, (3GdTQbGhjs ((3YeGf(B:s (3GKQGA ddfTQ h GdJhRjY(B,s, 2009)
(3fXGe GdeMGSHI GdeGdjI , GdbjO h GdJQMjd h GYOGO ejRGf GdeQGLYI , bjhO GdJShjI h GSJceGd GdOhQI GdeMGSHjI , GdeMGSHI aj GdefTBJ GdJLGQjI h fXGe GdLQO GdeSJeQ , GdeMGSHI Yf GdeNRhf GdSdYj h fXGe GdLQO GdOhQj , fXe GdeYdheGJ GdeMGSHjI h GdjhejGJ GdNGUI aj Xd fXGej GdLQO GdeSJeQ h GdLQO GdOhQj , GdeMGSHI Yf GdGUhd GdKGHJI GdedehSI h GdehGQO GdWHjYjI h GdGUhd ZjQ GdedehSI , GdQbGHI GdOGNdjI h GdfbOjI HGdNRjfI h GdHfc h UfOhb GdeUQhaGJ GdfKQjI , GdeMGSHI Yf GdYedGA , Yf GdGhQGb GdeGdjI , Yf GdGdJRGeGJ GdeJOGhdI , Yf GdGdJRGeGJ WhjdI GdGLd h Yf GdGSJKeGQGJ h CNjQG bGFeI GdJOabGJ GdfbOjI(B.s
Keywords: (3GdeGdjIs; (3GdeMGSHIs